Beneficios, tasa de interés y libre empresa en el capitalismo contemporáneo - Smtthin, John (2002)
The paper suggests an approach to economic growth in a system with capitalistic soctal institutions, emphasizing the interaction of the real interest rate, the profit share, and the rate of growth oT autonomous demand. The key relationship in the model is an interest-profit-wage frontier, the characteristics of which depend on the bargaining power of labour, monetary policy and technical change. One main result is that lower rates of interest will tend to increase both the growth rate an the share of entrepreneurial profit. Also, an increase in the growth of autonamons demand will increase the growth rate. However, in this case if the endogenous rate of increase in technical progress is not strong, the expansion tends rather to reduce the profit share. Án cxogenous improvement in technical progress increases both the growth rate and profitability.